دور تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمة المالية البريدية: دراسة حالة وحدة البريد الولائية - بسكرة - بن سماعين، حياة Bin Samain, Hayah; بوغديري، حكيمة Boughadiri, Hakimah (جامعة محمد خيضر بسكرة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
The aim of this study was to identify the role of information and communication technology in improving the quality of the postal financial service provided to the recipients through an analytical study of the postal unit of Biskra. we found that information and communication technology has a small contribution to the improvement of the quality of the postal service, not because of the lack of means. However, the reluctance of the customers of the Post Office in Biskra is due to the use of magnetic cards and the absence of quality service dimensions: the concrete aspects, the degree of reliability, degree of response, degree of safety, degree of empathy.
هدفت هذه الدراسة إلى التعرف على دور تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمة المالية البريدية المقدمة إلى متلقي الخدمة، من خلال إجراء دراسة تحليلية لوحدة البريد الولائية بسكرة، حيث توصلنا إلى أن تكنولوجيا المعلومات والاتصال تساهم بدرجة ضعيفة في تحسين جودة الخدمة المالية البريدية لا لعدم توفر الوسائل اللازمة لذلك لكن يعود عزوف زبائن وحدة البريد الولائية بسكرة عن استخدام البطاقات المغناطيسية راجع لعدم توفر أبعاد جودة الخدمة: الجوانب الملموسة، درجة الاعتمادية، درجة الاستجابة، درجة الأمان، درجة التعاطف.
Keywords: تكنولوجيا المعلومات -- الخدمات المالية -- الخدمات البريدية -- الأداء المؤسسى -- وحدة البريد الولائية -- ولاية بسكرة -- الجزائر